The impact of climate change on the economy of the Parnaíba river basin - Gomes, Sepúlveda Fabrício (2020)
The present work used a deterministic growth model made by Li and Swain to simulate the economic variables of the Parnaíba River Basin in diﬀerent scenarios of water availability. The region in which the Parnbaíba River Basin is not considered a developed region and current management models do not make long run forecasts for the hydrographic demands of the basin. In the scenario with a slight reduction ( 10% of reduction) in water availability, no signiﬁcant diﬀerence was found in relation to the standard scenario in the region. With more severe reductions about 38,5%, which is considered as a reduced inﬂow in dry times, the well-being and growth of the region is compromised. Keywords: Growth model. Water. Long run.